Egg excretion patterns of soil-transmitted helminth infections in humans following albendazole-ivermectin and albendazole treatment. - Sophie Welsche; Pierre H H Schneeberger; Jan Hattendorf; Somphou Sayasone; Eveline Hürlimann; Jennifer Keiser (PLoS Neglected Tropical Diseases)
Background Control efforts of soil-transmitted helminthiases rely primarily on large scale administration of anthelminthic drugs. The assessment of drug efficacies and understanding of drug behavior is pivotal to the evaluation of treatment successes, both in preventive chemo-therapy programs as well as in research of novel treatment options. The current WHO guidelines recommend an interval of 14-21 days between the treatment and follow-up, yet no in-depth analysis of egg excretion patterns of Trichuris trichiura after treatment has been conducted to date. Methods Within the framework of a multi-country trial to assess the efficacy and safety of albendazole-ivermectin combination therapy vs albendazole monotherapy against T. trichiura infections, we conducted a study collecting daily stool samples over the period of 28 days post-treatment in 87 participants in Pak Khan, Lao PDR. Egg counts were derived by duplicate Kato-Katz on-site for T. trichiura, hookworm and Ascaris lumbricoides and stool sample aliquots were subsequently analyzed by qPCR for the detection of T. trichiura infections. Sensitivity and specificity was calculated for each day separately using data derived by Kato-Katz to determine the optimal timepoint at which to assess drug efficacy. Results Egg excretion patterns varied across treatment arms. For T. trichiura, only the albendazole-ivermectin treatment led to a considerable reduction in mean egg counts, whereas both treatments reduced hookworm egg counts and A. lumbricoides were cleared in all participants after day 7. For T. trichiura, we found sensitivity to be highest at days 18 and 22 when using egg counts as outcome and days 19 and 24 when using qPCR. Specificity was high (>0.9) from day 14 onwards. For hookworm, the highest sensitivity and specificity were found at days 17 and 25, respectively. Conclusions Based on our study, the ideal time period to assess drug efficacy for soil-transmitted helminth infections would be between day 18 and 24. The current WHO recommendation of 14 to 21 days is likely to yield acceptable outcome measures for soil-transmitted helminth infections. Trial registration NCT03527732.